2018
DOI: 10.24230/kjiop.v31i1.249-279
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between role overload and work engagement among employees

Abstract: This study investigated the mechanisms of the relationships between role overload and three dimensions of work engagement. It was hypothesized that psychological detachment would mediate the relationship between role overload and work engagement, and the indirect effect of role overload on work engagement through psychological detachment would be conditional on job crafting and marital status. Consistent with our hypothesis, the moderating effect of job crafting on the relationship between role overload and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…First, our results confirmed Hypothesis 1 , which stated that role overload negatively affects work engagement. Our findings were similar to those of earlier studies (Bakker & Sanz‐Vergel, 2013 ; Kim et al, 2018 ). This could be due to role overload being harmful, causing stress, exhaustion and degrading care (Dasgupta, 2012 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…First, our results confirmed Hypothesis 1 , which stated that role overload negatively affects work engagement. Our findings were similar to those of earlier studies (Bakker & Sanz‐Vergel, 2013 ; Kim et al, 2018 ). This could be due to role overload being harmful, causing stress, exhaustion and degrading care (Dasgupta, 2012 ).…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, role overload will generate negative emotions and perceptions, leading to passive and emotion-centred coping, which is reflected in reduced work engagement (Crawford et al, 2010). Based on the aforementioned insights, a negative role overload-work engagement correlation has been proposed and confirmed by researchers (Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies have demonstrated that marital status moderated the effect of role overload on its outcomes by providing additional resources. For example, marital status played moderating role in the relationship between role overload and work engagement ( Kim et al, 2018 ), as well as the relationship between role overload and the work-family interface ( Vatharkar and Aggarwal-Gupta, 2020 ).…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%